Examining the Effect of Dry Resin on Moisture Sensitivity of Asphaltic Mixtures - Ghaffari Jajin, Morteza; Hamedi, Gholam Hossein (Civil Engineering Journal, 2018)
Moisture damage in asphaltic mixtures is defined by the loss of durability and resistance caused by the effect of moisture. The most common way to improve moisture damage in asphaltic mixtures is to use anti-strip additives. This study tended to use dry resin polymer additive to make a moisture-resistant asphaltic mixture. Two types of aggregate indicating different sensitivities against moisture were studied. In order to compare the effect of this material with other anti-strip additives, this study evaluated the effect of hydrated lime on reducing moisture damage and comparing its effect with dry resin polymer additive. The effect of these materials was evaluated by mechanical and thermodynamic concepts using indirect tensile ratio and surface free energy. The results indicated that dry resin polymer used in this study increased alkaline content and reduced acidic content of bituminous surface free energy, resulting in more adhesion between acidic aggregates which are more sensitive to resistance. It also improved bitumen-aggregate adhesion and reduced strip rate. Moreover, hydrated lime as an aggregate anti-strip agent and dry resin polymer as a bituminous modifier significantly increased the resistance of warm asphalt mixtures against moisture. The results of this study show that dry resin polymer can be used as an anti-strip agent instead of hydrated lime with operational problems.